Dietary Omega-3 Fatty Acids Alter Hepatic Lipid Oxidation and Oxidative Stress Markers in Postpartum Dairy Cows - Storani, Gino (2026)
Omega-3 (ω−3) polyunsaturated fatty acids are well recognized for their potential to influence metabolic adaptation in dairy cows during the transition period. This study evaluated the effects of calcium salts enriched with ω−3 fatty acids, including α-linolenic acid and long-chain ω−3 fatty acids such as eicosapentaenoic and docosahexaenoic acids, on hepatic lipid metabolism-related proteins, oxidative stress biomarkers, and liver function in postpartum dairy cows. Prior to calving, cows received a total mixed ration supplemented with 0.400 kg dry matter (DM)/day of calcium salts derived from a flaxseed oil–fish oil mixture (60:40). After calving, cows were fed a partial mixed ration and received 0.650 kg DM/day of the same supplement mixed with a commercial concentrate during milking. Control cows received isoenergetic diets in which calcium salts were replaced with ground corn. Blood, urine, and liver samples were collected at −21 days relative to calving (used as a baseline covariate) and at +7, and +21 (±3) days postpartum, when treatment effects were evaluated. No differences were observed between treatments in conventional biochemical markers of liver function or hepatic triacylglycerol concentration. Plasma malondialdehyde concentrations were higher in ω−3-supplemented cows, whereas other oxidative stress parameters were not affected. Supplementation with ω−3 fatty acids was associated with changes in the abundance of selected hepatic proteins involved in fatty acid metabolism, including increased acyl-CoA oxidase 1 and 3-hydroxy-3-methylglutaryl-CoA synthase and reduced diacylglycerol O-acyltransferase 1 abundance, whereas carnitine palmitoyltransferase 1 and peroxisome proliferator-activated receptor alpha abundance were not affected. These findings indicate that ω−3-enriched calcium salts induce molecular adjustments in hepatic lipid metabolism during early lactation without evidence of adverse effects on liver function.